A Stochastic Model for Wolf's Sunspot Number - Rui Goncalves (2011)
We present a simplified cycle model, using the available data, for the monthly sunspot number random variables X-t(t=1)(133), where 133 is taken as the mean duration of the Schwabe's cycle. We present a fit for the mean and standard deviation of X-t. In the descending and ascending phases, we analyse the probability histogram of the monthly sunspot number fluctuations.